STANDAR PENYUSUTAN DOKUMEN REKAM MEDIS DI PUSKESMAS KEDUNGMUNDU KOTA SEMARANG TAHUN 2019 - Retno Astuti Setijaningsih; Jaka Prasetya (VISIKES: Jurnal Kesehatan Masyarakat, 2020)
Public Health Center (PHC) is a central development in the working area. Its orientation is the safety of the patient. For it takes depreciation medical record documents to reduce the burden of storage and workload file clerk. Therefore, medical record documents more easily and quickly traceable.It is associated with patient’s medical record documentstracking speed. Result for The PHC obtained their medical record documents missfile accident due to stacking file. The research desain is a case study. Cross sectional approaching with observation and interviews as the method of collecting data. Processing data using collecting, editing, and tabulating. Then the data were analyzed descriptively. Generally, numbering system with applied to the patient’s family health centers folder is Unit Numbering System (UNS). PHC, in general, already implementing Terminal Digit Filing (TDF) alignment system, but in Puskesmas Kedungmundu still apply Straight Numerical Filing (SNF). The retention system is decentralization. While Puskesmas Kedungmundu peciathas implemented centralized. Depreciation medical record documents has not been routinely performed and without documentation. Several PHC even do not perpetuate medical record documents as regulated on The Permenkes Nomor 269/Menkes/PER/III/2008. Medical record documents depreciation required the disease index, patient index, standard operating procedure, record retentions schedules and documentation. In addition, need to reform the medical record documents management to facilitate the implementation of depreciation. Keywords : medical record document, depreciation, public health center